A perfect getaway [videorecording (DVD)] - Twohy, David; Olyphant, Timothy; Jovovich, Milla; Sanchez, Kiele, 1977-; Zahn, Steve, 1968-; Hemsworth, Chris (Universal Studios Home Entertainment, 2009)
Cliff and Cydney are an adventurous young couple celebrating their honeymoon by backpacking to one of the most beautiful, and remote, beaches in Hawaii. Hiking the wild, secluded trails, they believe they have found paradise. But when the pair comes across a group of frightened hikers discussing the horrifying murder of another newlywed couple on the islands, they begin to question whether they should turn back. Unsure whether to stay or flee, Cliff and Cydney decide to join up with two other couples. This is when things begin to go terrifyingly wrong. Far from civilization or rescue, everyone begins to look like a threat and nobody knows whom to trust. Paradise becomes hell on earth as a brutal battle for survival begins.